Pharmacokinetics of a low dose and FDA‐labeled dose of diclazuril administered orally as a pelleted topdressing in adult horses. Issue 3 (20th October 2014) - Hunyadi, L.; Papich, M. G.; Pusterla, N.
Abstract : The purpose of this study was to determine the pharmacokinetics of the FDA‐approved labeled dose of diclazuril and compare it to a low dose in plasma and CSF in adult horses. During each research period, six healthy adult horses received 0.5 mg/kg of 1.56% diclazuril pellets (Protazil TM, Merck Animal Health) compared to the approved labeled dose of 1 mg/kg orally once in two separate phases. A dose of 0.5 mg/kg was calculated to each horse's weight. Blood was then collected immediately before diclazuril administration and then at regular intervals up to a 168 h. After the last blood collection following the single dose at hour 168, a once daily oral dose was administered for the next 10 days to ensure the drug's concentration reached steady‐state. To determine the CSF concentration at steady‐state, CSF samples were collected after the 9th oral dose. Blood was then collected after the 10th dose and then at regular intervals up to 168 h. A washout period of 4 weeks was allowed before repeating this protocol for the FDA‐labeled dose at 1 mg/kg. Plasma and CSF samples were analyzed by high‐pressure liquid chromatography. A one‐compartment pharmacokinetic model with first‐order oral absorption was fitted to the single administration data. Steady‐state pharmacokinetics was performed using noncompartmental analysis for steady‐state analysis. The mean (standard deviation) concentration of diclazuril in CSF following the low dose was 26 ng/mL (5 ng/mL), while CSF in the FDA‐labeled dose was 25 ng/mL (4 ng/mL), P = 0.3750. Substantial accumulation in plasma occurred at steady‐state after the 10th dose for both doses. The results of this study show that diclazuril pellets given at the approved label dose and a lower dose both produce similar plasma drug concentrations at steady‐state and attain plasma and CSF concentrations known to inhibit Sarcocystis neurona in cell culture.